Taxonomy and biology of a new species of Pincushion Millipede of the genus Monographis (Diplopoda: Polyxenidae) from Australia - Huynh, Cuong; Veenstra, Anneke (Zootaxa, 2013)
Monographis queenslandicus n. sp. is described from Brisbane, Queensland, Australia. The genus Monographis may be divided into two groups based on the arrangement of sensilla on the 6th antennal article. Species with a crescent-shape arrangement are M. kraepelini, M. annandalei, M. baihualingensis, M. demangei and M. mirus; species with a triangular arrangement are M. tamoyensis, M. yunnanensis and M. queenslandicus n. sp.